Method for purifying quartz sand by fluorine-free organic acid synergistic leaching
Patent Information
- Application Number
- CN202611188193.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
氟离子虽能有效破坏硅氧键,但废液处理成本高昂,更对反应釜、管道等金属材质造成剧烈晶间腐蚀,大幅增加了工业化生产的设备维护门槛与安全风险,为此,针对上述描述中提出的问题,本发明提出一种无氟有机酸协同浸出提纯石英砂的方法
1.本发明中改性水杨酸通过引入含孤对电子的膦酸酯基团(P=O与P-OH),在微波辅助加热条件下即能原位螯合草酸-氯化铁体系中的Fe3+,具有更强氧化-络合协同效应,能够特异性地攻击石英解理面中杂质原子的悬空键,在不依赖氟离子刻蚀的前提下,显著降低石英骨架内Al3+、Fe3+等类质同象取代杂质的脱除活化能,使常规酸浸无法触及的结构性杂质在液相阶段即被预活化和预剥离,有效避免了单纯物理酸洗的反复无效操作。
Smart Images

Figure CN123002860A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of quartz sand purification technology, specifically to a method for purifying quartz sand by synergistic leaching with fluorine-free organic acids. Background Technology
[0002] High-purity quartz sand is a core basic material in photovoltaics, electronic information, high-end optics, semiconductor lighting and other fields. Its SiO2 purity, impurity content and structural integrity directly determine the performance and service life of downstream products. At present, the industrial production of high-purity quartz sand mainly uses natural quartz ore as raw material. Impurities such as aluminum, iron, calcium, magnesium and alkali metals in the quartz lattice and surface are removed through processes such as crushing, roasting, magnetic separation and acid leaching to achieve mineral purification.
[0003] Traditional high-purity quartz sand preparation often relies on hydrofluoric acid (HF) or fluoride-containing salts as leaching aids. While fluoride ions can effectively break silicon-oxygen bonds, wastewater treatment is costly and causes severe intergranular corrosion to metal materials such as reactors and pipelines, significantly increasing the equipment maintenance threshold and safety risks in industrial production. Therefore, to address the problems described above, this invention proposes a method for purifying quartz sand through leaching with fluoride-free organic acids. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method for synergistic leaching and purification of quartz sand with fluorine-free organic acids, so as to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for purifying quartz sand by synergistic leaching with fluorine-free organic acids includes the following steps: S1. Add oxalic acid and modified salicylic acid to methanol and stir until completely dissolved. Add ferric chloride and stir until dissolved to obtain an acid solution. Add quartz sand to the acid solution and react under sealed conditions at 50-55℃ for 3-4 hours. After the reaction is completed, cool to room temperature and wash with deionized water until the pH of the filtrate is 6-7 to obtain acid-impregnated quartz sand.
[0006] S2. Mix the acid-impregnated quartz sand with the modified chlorinating agent and calcine it in a microwave calcination furnace. Set the microwave frequency to 2.4-2.5 GHz, the calcination temperature to 850-950 ℃, the holding time to 2-3 h, and the heating rate to 15-20 ℃ / min. After calcination, cool to room temperature and wash with deionized water to pH 6-7 to obtain high-purity quartz sand.
[0007] Modified salicylic acid is prepared through the following steps: S11. Add salicylic acid, diisopropyl phosphite, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to dichloromethane, mix and place in a microwave reactor, set the radiation power to 800-850W, and react at room temperature for 3-4 hours.
[0008] S12. After the reaction is complete, the filtrate is filtered. The filtrate is then distilled under reduced pressure to remove dichloromethane, yielding a crude product. The crude product is then purified to obtain a phosphonate derivative.
[0009] S13. Dissolve the phosphonate derivative in HCl solution and stir at 60-65℃ for 2-2.5 h for hydrolysis. After hydrolysis, wash with deionized water, filter, and vacuum dry to obtain modified salicylic acid.
[0010] Furthermore, the modified chlorinating agent in S2 is prepared through the following steps: S21. Grind and mix ammonium chloride and ammonium sulfate for 25-30 minutes to obtain a mixed salt. Dissolve the mixed salt in deionized water and stir at 50-60℃ until completely dissolved to obtain a mixed salt solution. Dissolve cerium nitrate and lanthanum nitrate in deionized water to obtain a rare earth solution. Add the rare earth solution dropwise to the composite salt solution and stir for 25-30 minutes to obtain a mixed solution.
[0011] S22. Evaporate the mixed solution at 80-90℃ to crystallize. After the water has been completely evaporated, take out the crystallized product, dry, grind and sieve the crystallized product to obtain composite salt powder.
[0012] S23. Dissolve the composite salt powder in deionized water and stir at 50-60℃. Add activated carbon powder and ultrasonically disperse for 15-20 min to obtain a suspension. Spray granulate the suspension to obtain composite particles. Under nitrogen protection, heat the composite particles to 300-320℃ at 3-5℃ / min and keep them at that temperature for 25-30 min to obtain a modified chlorinating agent.
[0013] Furthermore, in S1, the mass ratio of oxalic acid, modified salicylic acid, methanol and ferric chloride is 1:(0.6-0.8):(30-40):(0.04-0.08), and the mass ratio of quartz sand and acid solution is 1:(4-6).
[0014] Furthermore, the mass ratio of acid-leached quartz sand to modified chlorinating agent in S2 is 1:(0.04-0.06).
[0015] Furthermore, the mass ratio of salicylic acid, diisopropyl phosphite, dicyclohexylcarbodiimide, 4-dimethylaminopyridine to dichloromethane in S11 is 1: (0.95-1.05): (1.1-1.3): (0.1-0.2): (2-3).
[0016] Furthermore, the mass ratio of the phosphonate derivative to the HCl solution in S13 is 1:(2-3).
[0017] Furthermore, in S21, the mass ratio of ammonium chloride to ammonium sulfate is 1:(0.4-0.5), and the mass ratio of the mixed salt to deionized water is 1:(2-3).
[0018] Furthermore, in S21, the mass ratio of cerium nitrate, lanthanum nitrate and deionized water is 1:(0.6-0.7):(60-80), and the mass ratio of rare earth solution to complex salt solution is 1:(8-12).
[0019] Furthermore, in S23, the mass ratio of composite salt powder, deionized water and activated carbon powder is 1:(1.2-1.8):(0.08-0.12).
[0020] Furthermore, the process parameters in S23 are: inlet temperature 180℃, outlet temperature 80-85℃, feed rate 5-10mL / min, and atomization pressure 0.2-0.3MPa.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In this invention, modified salicylic acid, by introducing phosphonate groups (P=O and P-OH) containing lone pair electrons, can in situ chelate Fe in the oxalic acid-ferric chloride system under microwave-assisted heating conditions. 3+ It exhibits a stronger oxidation-complexation synergistic effect, capable of specifically attacking dangling bonds of impurity atoms in quartz cleavage planes, and significantly reducing Al within the quartz framework without relying on fluoride ion etching. 3+ Fe 3+ The removal activation energy of isomorphic substitution impurities allows structural impurities that cannot be reached by conventional acid leaching to be pre-activated and pre-stripped in the liquid phase, effectively avoiding the repeated ineffective operation of simple physical acid washing.
[0022] 2. In this invention, the modified chlorinating agent uses activated carbon as a porous carrier and microwave absorption medium. Rare earth nitrates and ammonium chloride / ammonium sulfate are co-crystallized and loaded onto it. During the microwave roasting stage, the thermoelectric effect generated by the activated carbon and the catalytic synergy of the 4f electron orbitals of rare earth elements delay the concentrated explosive decomposition of the chlorinating agent and prolong the effective chlorine release window. This mechanism ensures that a sufficient and stable high concentration of active chlorine free radicals is maintained throughout the roasting process. This forces the impurities (such as alkali metal chlorides and transition metal complexes) remaining in the closed pores after acid leaching to continuously transform into the high vapor pressure gas phase and escape in time. This eliminates the risk of high-temperature phase deterioration caused by excessive heating due to the complete volatilization of the chlorinating agent in traditional processes. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of the preparation process of high-purity quartz sand in this invention; Figure 2 This is a schematic diagram of the preparation process of modified salicylic acid in this invention; Figure 3 This is a schematic diagram of the preparation process of the modified chlorinating agent in this invention; Figure 4 These are scanning electron microscope (SEM) images of the quartz sand before and after acid leaching in Example 1. Figure 4 (a) is a scanning electron microscope image of the quartz sand before acid leaching. Figure 4 (b) is a scanning electron microscope image of high-purity quartz sand after acid leaching; Figure 5 The image shows the Raman spectrum of the high-purity quartz sand after acid leaching in Example 1. Detailed Implementation
[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0025] Please see Figures 1-5 The present invention provides a technical solution: Example 1: A method for purifying quartz sand by synergistic leaching with fluorine-free organic acids includes the following steps: I. Preparation of modified salicylic acid: S11. Weigh out 10g of salicylic acid, 9.5g of diisopropyl phosphite, 11g of dicyclohexylcarbodiimide, and 1g of 4-dimethylaminopyridine, add them to 20g of dichloromethane, mix them, and place them in a microwave reactor. Set the radiation power to 800W and react at room temperature for 3h.
[0026] S12. After the reaction is complete, filter to remove the dicyclohexylurea byproduct, collect the filtrate, and remove dichloromethane by vacuum distillation to obtain the crude product. The crude product is purified by silica gel column chromatography (eluent is ethyl acetate and petroleum ether in a volume ratio of 1:3) to obtain the phosphonate derivative.
[0027] S13. Take 10g of phosphonate derivative, dissolve it in 20g of 6mol / L HCl solution, stir and hydrolyze at 60℃ for 2h. After hydrolysis, wash with deionized water until neutral, filter, and vacuum dry to obtain modified salicylic acid.
[0028] II. Preparation of modified chlorinating agents: S21. Weigh 10g of ammonium chloride and 4g of ammonium sulfate, grind and mix for 25 minutes to obtain a mixed salt. Dissolve 14g of the mixed salt in 28g of deionized water and stir at 50℃ until completely dissolved to obtain a mixed salt solution.
[0029] Weigh out 0.1g of cerium nitrate and 0.06g of lanthanum nitrate, respectively, and dissolve them in 6g of deionized water to obtain a rare earth solution. Add 4g of the rare earth solution dropwise to 32g of mixed salt solution and stir for 25min to obtain a mixed solution.
[0030] S22. Evaporate the mixed solution at 80℃ to crystallize. After the water is completely evaporated, take out the crystallized product, dry it at 105℃ for 2 hours, grind it through a 150-mesh sieve, and obtain the composite salt powder.
[0031] S23. Dissolve 10g of composite salt powder in 12g of deionized water and stir at 50℃. Add 0.8g of activated carbon powder and ultrasonically disperse for 15min to obtain a suspension. Spray granulation of the suspension (inlet temperature 180℃, outlet temperature 80℃, feed rate 5mL / min, atomization pressure 0.2MPa) to obtain composite particles. Place the composite particles in a tube furnace and heat to 300℃ at 3℃ / min under nitrogen protection, and hold for 25min to obtain the modified chlorinating agent.
[0032] III. Purification of Quartz Sand: S1. Add 1g of oxalic acid and 0.6g of modified salicylic acid to 30.0g of methanol and stir until completely dissolved. Add 0.04g of ferric chloride as an oxidation-complexation catalyst and continue stirring at 25℃ to dissolve, obtaining an acid solution. Add 5g of quartz sand to 20g of acid solution and react at 50℃ under sealed conditions for 3h. After the reaction is completed, cool to room temperature and wash with deionized water until the pH of the filtrate is 6 to obtain acid-leached quartz sand.
[0033] S2. Weigh 4g of acid-leached quartz sand and 0.16g of modified chlorinating agent, mix them evenly and place them in a microwave roasting furnace. Set the microwave frequency to 2.4GHz, the roasting temperature to 850℃, the holding time to 2h, and the heating rate to 15℃ / min. After roasting, cool to room temperature and wash with deionized water until the pH is 6 to obtain high-purity quartz sand.
[0034] Example 2: A method for purifying quartz sand by synergistic leaching with fluorine-free organic acids includes the following steps: I. Preparation of modified salicylic acid: S11. Weigh out 10g of salicylic acid, 10g of diisopropyl phosphite, 12g of dicyclohexylcarbodiimide, and 1.5g of 4-dimethylaminopyridine, add them to 25g of dichloromethane, mix them, and place them in a microwave reactor. Set the radiation power to 830W and react at room temperature for 3.5h.
[0035] S12. After the reaction is complete, filter to remove the dicyclohexylurea byproduct, collect the filtrate, and remove dichloromethane by vacuum distillation to obtain the crude product. The crude product is purified by silica gel column chromatography (eluent is ethyl acetate and petroleum ether in a volume ratio of 1:3) to obtain the phosphonate derivative.
[0036] S13. Take 10g of phosphonate derivative, dissolve it in 25g of 6mol / L HCl solution, stir and hydrolyze at 63℃ for 2.3h. After hydrolysis, wash with deionized water until neutral, filter, and vacuum dry to obtain modified salicylic acid.
[0037] II. Preparation of modified chlorinating agents: S21. Weigh 10g of ammonium chloride and 4.5g of ammonium sulfate, grind and mix for 28 minutes to obtain a mixed salt. Dissolve 14g of the mixed salt in 35g of deionized water and stir at 55℃ until completely dissolved to obtain a mixed salt solution.
[0038] Weigh out 0.1g of cerium nitrate and 0.06g of lanthanum nitrate, respectively, and dissolve them in 7g of deionized water to obtain a rare earth solution. Add 4g of the rare earth solution dropwise to 40g of mixed salt solution and stir for 28min to obtain a mixed solution.
[0039] S22. Evaporate the mixed solution at 85°C to crystallize. After the water is completely evaporated, take out the crystallized product, dry it at 105°C for 2 hours, grind it through a 150-mesh sieve, and obtain the composite salt powder.
[0040] S23. Dissolve 10g of composite salt powder in 16g of deionized water and stir at 55℃. Add 1g of activated carbon powder and ultrasonically disperse for 18min to obtain a suspension. Spray granulation of the suspension (inlet temperature 180℃, outlet temperature 83℃, feed rate 8mL / min, atomization pressure 0.2MPa) to obtain composite particles. Place the composite particles in a tube furnace and heat to 310℃ at 4℃ / min under nitrogen protection, and hold for 28min to obtain the modified chlorinating agent.
[0041] III. Purification of Quartz Sand: S1. Add 1g of oxalic acid and 0.7g of modified salicylic acid to 35g of methanol and stir until completely dissolved. Add 0.06g of ferric chloride as an oxidation-complexation catalyst and continue stirring at 25℃ to dissolve, obtaining an acid solution. Add 5g of quartz sand to 25g of the acid solution and react at 53℃ under sealed conditions for 3.5h. After the reaction is completed, cool to room temperature and wash with deionized water until the pH of the filtrate is 6.5 to obtain acid-leached quartz sand.
[0042] S2. Weigh 4g of acid-leached quartz sand and 0.2g of modified chlorinating agent, mix them evenly and place them in a microwave roasting furnace. Set the microwave frequency to 2.4GHz, the roasting temperature to 900℃, the holding time to 2.5h, and the heating rate to 18℃ / min. After roasting, cool to room temperature and wash with deionized water until the pH reaches 6.5 to obtain high-purity quartz sand.
[0043] Example 3: A method for purifying quartz sand by synergistic leaching with fluorine-free organic acids includes the following steps: I. Preparation of modified salicylic acid: S11. Weigh out 10g of salicylic acid, 10.5g of diisopropyl phosphite, 13g of dicyclohexylcarbodiimide, and 2g of 4-dimethylaminopyridine, add them to 30g of dichloromethane, mix them, and place them in a microwave reactor. Set the radiation power to 850W and react at room temperature for 4 hours.
[0044] S12. After the reaction is complete, filter to remove the dicyclohexylurea byproduct, collect the filtrate, and remove dichloromethane by vacuum distillation to obtain the crude product. The crude product is purified by silica gel column chromatography (eluent is ethyl acetate and petroleum ether in a volume ratio of 1:3) to obtain the phosphonate derivative.
[0045] S13. Take 10g of phosphonate derivative, dissolve it in 30g of 6mol / L HCl solution, stir and hydrolyze at 65℃ for 2.5h. After hydrolysis, wash with deionized water until neutral, filter, and vacuum dry to obtain modified salicylic acid.
[0046] II. Preparation of modified chlorinating agents: S21. Weigh 10g of ammonium chloride and 5g of ammonium sulfate, grind and mix for 30 minutes to obtain a mixed salt. Dissolve 15g of the mixed salt in 45g of deionized water and stir at 60℃ until completely dissolved to obtain a mixed salt solution.
[0047] Weigh out 0.1g of cerium nitrate and 0.07g of lanthanum nitrate, respectively, and dissolve them in 8g of deionized water to obtain a rare earth solution. Add 4g of the rare earth solution dropwise to 48g of the mixed salt solution and stir for 30min to obtain a mixed solution.
[0048] S22. Evaporate the mixed solution at 90℃ to crystallize. After the water is completely evaporated, take out the crystallized product, dry it at 105℃ for 2 hours, grind it through a 150-mesh sieve, and obtain the composite salt powder.
[0049] S23. Dissolve 10g of composite salt powder in 18g of deionized water and stir at 60℃. Add 1.2g of activated carbon powder and ultrasonically disperse for 20min to obtain a suspension. Spray granulation of the suspension (inlet temperature 180℃, outlet temperature 85℃, feed rate 10mL / min, atomization pressure 0.3MPa) to obtain composite particles. Place the composite particles in a tube furnace and heat to 320℃ at 5℃ / min under nitrogen protection, and hold for 30min to obtain the modified chlorinating agent.
[0050] III. Purification of Quartz Sand: S1. Add 1g of oxalic acid and 0.8g of modified salicylic acid to 40g of methanol and stir until completely dissolved. Add 0.08g of ferric chloride as an oxidation-complexation catalyst and continue stirring at 25℃ to dissolve, obtaining an acid solution. Add 5g of quartz sand to 30g of the acid solution and react at 55℃ under sealed conditions for 4h. After the reaction is completed, cool to room temperature and wash with deionized water until the pH of the filtrate is 7 to obtain acid-leached quartz sand.
[0051] S2. Weigh 4g of acid-leached quartz sand and 0.24g of modified chlorinating agent, mix them evenly and place them in a microwave roasting furnace. Set the microwave frequency to 2.5GHz, the roasting temperature to 950℃, the holding time to 3h, and the heating rate to 20℃ / min. After roasting, cool to room temperature and wash with deionized water until the pH is 7 to obtain high-purity quartz sand.
[0052] Comparative Example 1: Comparative Example 1 differs from Example 1 in that the modified salicylic acid is replaced with an equal mass of salicylic acid, and the remaining steps are exactly the same as in Example 1.
[0053] Comparative Example 2: Comparative Example 2 differs from Example 1 in that the modified chlorinating agent is replaced with an equal mass of ammonium chloride, while the remaining steps are exactly the same as in Example 1.
[0054] Comparative Example 3: Comparative Example 3 differs from Example 1 in that the modified salicylic acid is replaced with an equal mass of salicylic acid, and the modified chlorinating agent is replaced with an equal mass of ammonium chloride. The remaining steps are exactly the same as in Example 1.
[0055] The high-purity quartz sand samples prepared in Example 1 and Comparative Examples 1-3 were subjected to the following tests: Chemical purity testing: The content of SiO2, Al2O3, TFe, Na2O, K2O, CaO, MgO, P2O5 and other impurities were determined to evaluate the purification and impurity removal effect. 1.5g of dried 200-mesh quartz powder was weighed, pressed into a pellet on a boric acid substrate, and held at 20MPa for 30s to form a flat test piece. Wavelength dispersive X-ray fluorescence spectrometry (WD-XRF) was used for detection. The detection limit (LOD) of iron was ≤2ppm and the quantification limit (LOQ) was ≤6ppm. The elemental intensity curve was calibrated with a standard quartz sample. The pellet was placed in the sample chamber, vacuumed, and the detection mode was set to: quantitative analysis of all elements in ore, detection time 15min / sample. The mass percentage of each oxide was automatically output, and the purity of SiO2 and the total impurity content were recorded. The specific test results are shown in Table 1. Table 1: Purity Test Table for High-Purity Quartz Sand Table 1 shows that the main components and impurity elements of each sample were quantitatively analyzed in the form of oxides. The listed items are the main detectable components. The remaining undetected or trace components, which resulted in a total of less than 100%, do not affect the purity ranking and purification effect evaluation. As can be seen from the data in Table 1, the quartz sand prepared by the modified salicylic acid and modified chlorinating agent combined purification process of the present invention in the three sets of examples all achieved a SiO2 purity of over 99.9%, and the content of various metal oxide impurities remained at an extremely low level overall. Among them, the process conditions of Example 2 were optimal, with a SiO2 purity of 99.952%, and all impurity indicators such as TFe, Al2O3, alkali metals, and alkaline earth metals were the lowest among the three sets of examples. The purification effects of Examples 1 and 3 were slightly worse than those of Example 2, but the difference between the two was small. This indicates that there is an optimal range for the ratio of oxalic acid, modified salicylic acid, and ferric chloride, as well as parameters such as microwave roasting temperature and holding time. Parameters that are too high or too low will slightly reduce the impurity removal efficiency.
[0056] The three comparative groups did not use a complete modified reagent system, and the purity of SiO2 was reduced to the 98% range in all cases, showing a significant performance difference compared to the examples. Comparative Example 1 simply replaced the modified salicylic acid with ordinary salicylic acid, lacking phosphonate chelating groups, making it difficult to activate Al in the crystal lattice. 3+ Fe 3+ The levels of Al2O3 and TFe impurities increased significantly, while SiO2 decreased to 98.725%. Comparative Example 2 used only ordinary ammonium chloride to replace the modified chlorinating agent, lacking the rare earth catalysis and activated carbon slow-release chlorine free radical effect. The removal ability of alkali metal and alkaline earth metal impurities was significantly reduced, and the purity was further reduced to 98.562%. Comparative Example 3, by replacing both core modifying agents, completely lost the dual advantages of liquid-phase complexation for impurity removal and high-temperature chlorination for lattice impurity removal. The content of all impurities was the highest among all samples, with SiO2 at only 98.134%, resulting in the worst purification effect.
[0057] Comparing the overall impurity distribution pattern, Al2O3 is the most difficult core impurity to remove from quartz. The modified salicylic acid of this invention can pre-exfoliate aluminum and iron impurities in the lattice during the liquid phase, and the microwave roasting of the rare earth-loaded modified chlorinating agent can continuously remove residual alkali metal impurities in the closed pores. The two have a significant synergistic effect. It is impossible to prepare high-purity quartz sand by only improving the reagent or without modification treatment, which verifies the creativity and superiority of the reagent system and process combination of this invention.
[0058] Figure 4 These are scanning electron microscope (SEM) images of the quartz sand before and after acid leaching in Example 1. Figure 4 As shown in (a), the surface of the quartz particles is rough and uneven, with a large number of flaky clay minerals and fine iron oxide particles adhering to the grain surface and grain boundary gaps. There are obvious agglomerated impurity clusters, the grain boundaries are filled and covered by impurities, the grain boundary dissolution grooves are not obvious, and the particle surface is severely uneven, with a large number of micron-sized protrusions and impurity inclusions. The impurities (Al, Fe, alkali metal minerals) are tightly adhered to the quartz surface and are difficult to remove with conventional cleaning, which is the main reason restricting the purity of the quartz. Figure 4 As can be seen in (b), the surface cleanliness of high-purity quartz sand is greatly improved. The clay and iron impurities attached to the surface are basically completely eliminated, there are no obvious impurity agglomerates, the grain boundaries are clearly exposed, and uniform and fine selective dissolution grooves appear. This proves that the modified organic acid can penetrate into the grain boundary and dissolve the metal impurities enriched in the grain boundary. The particles are generally flat, with only a small number of nano-sized micro-pits remaining. There is no large area of impurity coverage. The liquid phase complex leaching has an outstanding effect on the removal of surface and grain boundary impurities.
[0059] Figure 5 The image shows the Raman spectrum of the high-purity quartz sand after acid leaching in Example 1. The sample only shows the characteristic Raman peak of α-quartz: 123 cm⁻¹. -1 200cm -1 458.5cm -1 The three main peaks show no characteristic peaks of impurities such as illite, iron oxide, or aluminosilicate. The characteristic peaks are sharp and have stable baselines, with no obvious broadening or shifting. This indicates that the entire purification process does not damage the quartz Si-O-Si crystal framework and the crystal lattice is intact. The slight displacement of the main peaks is only due to the release of lattice stress after the removal of grain boundary impurities. There are no defects such as silicon-oxygen bond corrosion or phase transformation. The crystal structure of the product meets the requirements for high-purity quartz.
[0060] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for purifying quartz sand by synergistic leaching with fluorine-free organic acids, characterized in that, Includes the following steps: S1. Add oxalic acid and modified salicylic acid to methanol and stir until completely dissolved. Add ferric chloride and stir until dissolved to obtain an acid solution. Add quartz sand to the acid solution and react under sealed conditions at 50-55℃ for 3-4 hours. After the reaction is completed, cool to room temperature and wash with deionized water until the pH of the filtrate is 6-7 to obtain acid-leached quartz sand. S2. Mix the acid-etched quartz sand with the modified chlorinating agent and calcine it in a microwave calcination furnace. Set the microwave frequency to 2.4-2.5 GHz, the calcination temperature to 850-950 ℃, the holding time to 2-3 h, and the heating rate to 15-20 ℃ / min. After calcination, cool it to room temperature and wash it with deionized water to pH 6-7 to obtain high-purity quartz sand. Modified salicylic acid is prepared through the following steps: S11. Add salicylic acid, diisopropyl phosphite, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to dichloromethane, mix and place in a microwave reactor, set the radiation power to 800-850W, and react at room temperature for 3-4 hours. S12. After the reaction is complete, filter to obtain filtrate. Remove dichloromethane from the filtrate by vacuum distillation to obtain crude product. After purification, phosphonate derivative is obtained. S13. Dissolve the phosphonate derivative in HCl solution and stir at 60-65℃ for 2-2.5 h for hydrolysis. After hydrolysis, wash with deionized water, filter, and vacuum dry to obtain modified salicylic acid.
2. The method for purifying quartz sand by synergistic leaching with fluorine-free organic acids according to claim 1, characterized in that, The modified chlorinating agent in S2 is prepared through the following steps: S21. Grind and mix ammonium chloride and ammonium sulfate for 25-30 minutes to obtain a mixed salt. Dissolve the mixed salt in deionized water and stir at 50-60℃ until completely dissolved to obtain a mixed salt solution. Dissolve cerium nitrate and lanthanum nitrate in deionized water to obtain a rare earth solution. Add the rare earth solution dropwise to the composite salt solution and stir for 25-30 minutes to obtain a mixed solution. S22. Evaporate the mixed solution at 80-90℃ to crystallize. After the water is completely evaporated, take out the crystallized product, dry, grind and sieve the crystallized product to obtain composite salt powder. S23. Dissolve the composite salt powder in deionized water and stir at 50-60℃. Add activated carbon powder and ultrasonically disperse for 15-20 min to obtain a suspension. Spray granulate the suspension to obtain composite particles. Under nitrogen protection, heat the composite particles to 300-320℃ at 3-5℃ / min and keep them at that temperature for 25-30 min to obtain a modified chlorinating agent.
3. The method for purifying quartz sand by synergistic leaching with fluorine-free organic acids according to claim 1, characterized in that, In S1, the mass ratio of oxalic acid, modified salicylic acid, methanol and ferric chloride is 1:(0.6-0.8):(30-40):(0.04-0.08), and the mass ratio of quartz sand and acid solution is 1:(4-6).
4. The method for purifying quartz sand by synergistic leaching with fluorine-free organic acids according to claim 1, characterized in that, The mass ratio of acid-leached quartz sand to modified chlorinating agent in S2 is 1:(0.04-0.06).
5. The method for synergistic leaching and purification of quartz sand with fluorine-free organic acids according to claim 1, characterized in that, The mass ratio of salicylic acid, diisopropyl phosphite, dicyclohexylcarbodiimide, 4-dimethylaminopyridine to dichloromethane in S11 is 1: (0.95-1.05): (1.1-1.3): (0.1-0.2): (2-3).
6. The method for purifying quartz sand by synergistic leaching with fluorine-free organic acids according to claim 1, characterized in that, The mass ratio of the phosphonate derivative to the HCl solution in S13 is 1:(2-3).
7. The method for purifying quartz sand by synergistic leaching with fluorine-free organic acids according to claim 2, characterized in that, In S21, the mass ratio of ammonium chloride to ammonium sulfate is 1:(0.4-0.5), and the mass ratio of the mixed salt to deionized water is 1:(2-3).
8. The method for purifying quartz sand by synergistic leaching with fluorine-free organic acids according to claim 2, characterized in that, The mass ratio of cerium nitrate, lanthanum nitrate and deionized water in S21 is 1:(0.6-0.7):(60-80), and the mass ratio of rare earth solution to complex salt solution is 1:(8-12).
9. The method for synergistic leaching and purification of quartz sand with fluorine-free organic acids according to claim 2, characterized in that, The mass ratio of composite salt powder, deionized water and activated carbon powder in S23 is 1:(1.2-1.8):(0.08-0.12).
10. The method for synergistic leaching and purification of quartz sand with fluorine-free organic acids according to claim 2, characterized in that, The process parameters in S23 are: inlet temperature 180℃, outlet temperature 80-85℃, feed rate 5-10mL / min, and atomization pressure 0.2-0.3MPa.
